TRANSLATION ANALYSIS OF IDIOMATIC EXPRESSIONS IN NOVEL TO ALL THE BOYS I’VE LOVED BEFORE - Sekar Satiti Suci Adianti; Evert H. Hilman; Maftuchah Dwi Agustina (PROJECT (Professional Journal of English Education), 2022)
This research aims to analyze the translation strategies, syntactically and semantically, used by the translator from English to Indonesian and the translation quality assessment. Theories by Chesterman, and Nababan et al., along with other theories, were used to discover the answer in the analyzing process. The methods applied are descriptive qualitative and focus group discussion (FGD). The results of the translation strategies shows, the majorly used syntactic strategies is unit shift, whereas the most employed semantic strategies are paraphrase followed by trope change. Translation quality assessment wise, ten data shows less accuracy level and the overall data indicates high accuracy level, high acceptability level, and high readability level. Keywords:  Translation Analysis, Idiomatic Expressions, Novel